(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2012)
Language is a system of communication. In this broad sense, human language is a code that communicates meaning, as do other types of communication systems such as animal sounds and movements, traffic control signs and lights, human gestures and body language, and even computer source code and others. Human language is a system of communication that combines sounds with meanings to produce what people know and use as natural language. The goal of the linguist is to understand units of language, their possible rule governed combinations, and the conditions for how language is used, as well as the norms of correct and appropriate language for a given speech community. Although the linguistic study of language is well established, linguistics is something new for many jurors, judges, attorneys and other forensic specialists. Forensic linguistics is not a new field, but over the past few years it has become more structured and better defined within the academic and forensic communities. An understanding of language, linguistics, and the field of forensic linguistics will develop a more informed understanding of recent advances in the theory and method of forensic Linguistics.